Mass media and political modernity : an empirical study in five developing countries - Mukherjee, Bishwa Nath (Bhargava research monograph series ;)
Evaluation of the effect of mass media on the individual's level of political awareness, knowledge, and belief in new political ideologies; based on data collected from factory workers in India, Bangladesh, Nigeria, Chile, and Israel during 1963-1964.